Composition and structure of parasite communities in white bream Blicca bjoerkna from Lake Buyuk Akgol, Sakarya-Turkey - (:unkn) unknown (EGE UNIV, 2018)
No data on the parasites of Blicca bjoerkna have been reported to date from Lake Buyuk Akgol. Therefore, the current study aimed to investigate the composition and diversity of parasite component and infra-communities in this cyprinid fish from hypereutrophic Lake Buyuk Akgol. A total of 61 B. bjoerkna were examined between July 2016 and June 2017. All fishes were hosts to at least one parasite species from the following taxa: Trichodina sp., Epistylis sp. (Protozoa); Myxobolus sp. (Myxozoa); Dactylogyrus sphyrna, D. cornu, D. cornoides, D. distinguendus and Paradiplozoon homoion (Monogenea); Caryophyllaeus laticeps and Cestoda gen. sp. (Cestoidea); Diplostomum sp., Thylodelphys clavata and Posthodiplostomum cuticola (Digenea); Piscicola geometra (Hirudinea); Glochidium sp. (Mollusca) and Argulus foliaceus (Crustacea). Dominant species in the component community were Diplostomum sp., D. cornoides, and D. cornu. Totally 2063 metazoan parasite individuals were collected. Parasite infra-communities of B. bjoerkna infected 1-10 species and the mean species richness found was 5.3. The mean metazoan parasite diversity (Shannon's H index) was 2.08 and the Shannon-Wiener Evenness (E) had a mean value of 0.81. Identified parasite species in B. bjoerkna were the first records from Lake Buyuk Akgol.
Keywords: Parasite communities; Blicca bjoerkna; Lake Buyuk Akgol; GASTROINTESTINAL HELMINTH COMMUNITIES; SPECIES COMPOSITION; TOXICITY; EVENNESS; STREAM